The application of principle of res judicata and estopple in family law cases in Syariah court - Azzis, Nadia Murshida Abd (Linguistics and Culture Review, 2021)
This writing examines the Syariah court’s approach in applying the principle of res judicata and estoppel in family law cases in Syariah. With the existence of the legal provisions, there are still the unclear application of res judicata and the principle of estopple in terms of hearing mal cases especially the matter involved with a monetary claim for example mut’ah cases, child maintenance, and jointly acquired property. Although this principle has been understood by the legal practitioner, the synchronization between the principle of res judicata, estopple, and court procedure is yet to be scrutinized by the Courts. Thus, a qualitative study was carried out along with library research including decided cases in this research. The content analysis method is applied in data analysis. This study indicated that in arriving at a decision, Syariah Court indirectly applied these principles. However, the implementation of these principles should be highlighted to validate the principle of justice in Syariah Courts.